Sustainable Energy Governance in Developing Countries: A Case Study of Natural Gas Policy in Timor-Leste - Barreto, Denilson Tilman Da Silva; Sudibandriyo, Mahmud (International Ecsis Association, 2025)
The utilization of natural gas as a strategic resource for sustainable development in developing countries still faces multiple challenges, particularly in terms of equitable access and inclusive governance. This study aims to assess the sustainability of natural gas governance in Timor-Leste using the A4 framework (Availability, Accessibility, Affordability, Acceptability). A qualitative case study approach was employed, involving in-depth interviews with ten key stakeholders, including government officials, academics, energy company representatives, and local community members. Primary data were supported by the analysis of national policy documents and official petroleum sector reports, and examined through thematic analysis and source triangulation. The findings reveal a significant gap in perception between government and local communities across all four A4 indicators. While the government shows optimism regarding resource availability and technical feasibility, local communities report poor accessibility and affordability, having experienced little direct benefit. Public acceptability is rated as moderate, with limited participation and top-down communication approaches. The practical implication of this study highlights the need to shift the Petroleum Fund’s investment strategy toward domestic energy infrastructure and introduce inclusive subsidy policies. Theoretically, this study reinforces the importance of integrating natural resource theory, development economics, and investment strategy in shaping a fair and sustainable energy governance framework for post-conflict countries like Timor-Leste.